Emotion regulation difficulties interact with negative, not positive, emotional eating to strengthen relationships with disordered eating: An exploratory study. (1st March 2021) - Barnhart, Wesley R.; Braden, Abby L.; Price, Ellysia
Abstract: Disordered eating includes core eating disorder symptoms present in diverse populations. The extant literature has focused on associations between negative emotional eating and disordered eating to the exclusion of positive emotional eating. Emotion regulation may help explain relationships between emotional eating and disordered eating. Emotion regulation difficulties was examined as a moderator of relationships between negative and positive emotional eating and disordered eating including dietary restraint, eating, weight, and shape concerns, and global scores of disordered eating, a general index of disordered eating. A cross-sectional study was employed using a university student population in the United States. Participants completed surveys assessing negative (Dutch Eating Behavior Questionnaire; Emotional Appetite Questionnaire) and positive (Emotional Appetite Questionnaire) emotional eating, emotion regulation (Difficulties in Emotion Regulation Scale), and disordered eating (Eating Disorder Examination Questionnaire). Moderation analyses were calculated with emotion regulation difficulties as the moderator of relationships between negative and positive emotional eating and disordered eating. Across two separate measures of negative emotional eating, higher negative emotional eating was associated with higher weight concerns and global scores of disordered eating when emotion regulation difficulties was average and increased (+1 SD above average). Higher positive emotional eating was associated with lower dietary restraint and global scores of disordered eating when emotion regulation difficulties was decreased (−1 SD below average). Emotion regulation difficulties strengthened relationships between negative, not positive, emotional eating and disordered eating. Research and clinical implications for the contribution of emotional eating and emotion regulation on disordered eating were discussed.